Pengembangan Media Pembelajaran E-Book Interaktif Pada Materi Prakarya Untuk Meningkatkan Motivasi Belajar Dan Kreativitas Siswa - Surtini; Suratno; Ali, Muhammad (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
Students feel very enthusiastic about technology because of the presence of signals in the midst of residential areas, school environments and communities in Pengabuan. This can be seen from the involvement of the internet in craft learning which should be utilized well by teachers. This research aims to develop learning media, assess the feasibility of interactive craft e-book learning media and increase student learning motivation and creativity. The research method used is Research and Development. This development procedure refers to the Lee and Owens (2004) development model with the stages of Analysis, Needs Analysis, Front-End Analysis, Design, Development, Implementation, Evaluation. The result of this research and development is the development of interactive e-book learning media which is expressed procedurally and theoretically. Then this media was also declared feasible in practice. It can be concluded that interactive e-book media can increase student learning motivation and creativity.